Ripeness theory and the Cyprus conflict: understanding how comfortable stalemate and external pressure influence conflict resolution - Ersozer, Fadil; Sozen, Ahmet (Routledge Journals, Taylor & Francis Ltd, 2025)
This article examines the protracted Cyprus conflict through the lens of ripeness theory to explain why such conflicts persist despite extended negotiations with noticeable progress. It introduces the concept of a 'comfortable stalemate', which occurs when parties perceive the status quo as preferable to the costs of a negotiated settlement, making such compromise less attractive to Greek Cypriot, Turkish Cypriot, and Turkish leadership. Additionally, challenges in developing a mutually attractive compromise prevent a 'lock-in' effect during negotiations, allowing parties to revert to the status quo. External factors, such as geopolitical developments and energy discoveries in the Eastern Mediterranean, further reinforce the status quo, challenging the traditional focus of ripeness theory on internal dynamics. Therefore, the article proposes a new element to the theory called 'external pressure for resolution'. It also provides strategies for cultivating ripeness, including confidence-building measures and energy cooperation, offering insights for mediators and policymakers.
Keywords: Ripeness theory; comfortable stalemate; ethnopolitical conflict; Cyprus; T & uuml;rkiye; Eastern Mediterranean